Fractional-order brucellosis transmission model between interspecies with a saturated incidence rate - Yapışkan, Dilara; Eroğlu, Beyza Billur İskender (Fırat Evirgen, 2024)
In this study, brucellosis dynamics between interspecies are discussed with the Atangana-Baleanu fractional derivative to examine the transmission of brucellosis by its behavior. The recovered compartment, recruitment, and natural death rate for humans are considered for the fractional order model to analyze the transmission dynamics in more detail from an epidemiological point of view. Additionally, the saturated incidence rate is suggested for brucellosis as indirectly transmitted to individuals from the environment. By fixed point theory, it is verified that developed fractional transmission dynamics have a unique solution. The model under consideration employs the Adams-type predictor-corrector method for numerical solution. All comparative results are plotted by MATLAB.
Keywords: Biological Mathematics; Biyolojik Matematik